Programme Sahamalaza-Iles Radama de l’AEECL : étude et conservation des espèces menacées d’extinction de lémuriens dans le nord-ouest de Madagascar - Alice Dumoulin; Guy Randriatahina; Christoph Schwitzer (Revue de Primatologie)
The European Association for the Study and Conservation of Lemurs (Association Européenne pour l’Etude et la Conservation des Lémuriens, AEECL) is a consortium of European zoological gardens and universities who have joined forces to carry out conservation and research projects for Madagascar’s highly endangered lemurs since more than 30 years. AEECL implements or finances various different research projects to improve the scientific knowledge of lemurs. Information is essential to be able to develop comprehensive conservation and management plans to protect these animals. The work of AEECL has led to the implementation of a UNESCO Biosphere Reserve in Sahamalaza in 2001 and to the creation of the Sahamalaza-Iles Radama National Park in 2007. In addition to the research, AEECL is carrying out a community-based natural resource management plan in Sahamalaza. The Association has helped create local community associations in the villages of the four communes in the periphery of the protected area. Responsibility for the sustainable management of the natural resources is gradually handed over to the local communities.